2012
DOI: 10.1017/s0033291712001791
|View full text |Cite
|
Sign up to set email alerts
|

Thought disorder in mid-childhood as a predictor of adulthood diagnostic outcome: findings from the New York High-Risk Project

Abstract: These findings suggest that negative thought disorder may have a specific association with schizotypy, rather than a more general association with psychosis. The findings also support consideration of negative thought disorder as an endophenotypic indicator of a schizophrenia diathesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 43 publications
2
36
0
1
Order By: Relevance
“…79 An extensive body of empirical research, using a variety of measures to assess TD, has confirmed the presence of mild TD or odd speech in clinically unaffected relatives of SZ patients 42,44,[81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98] and in high-risk offspring. 20,[99][100][101][102][103][104][105][106] Notably, the biological relatives of SZ (RelSZ) adoptees have significantly higher TD scores than adoptive RelSZ. 92 Similarly, idiosyncratic verbalizations are significantly more prevalent in adopted biological offspring of SZ mothers than in adopted offspring of control mothers.…”
Section: Introductionmentioning
confidence: 99%
“…79 An extensive body of empirical research, using a variety of measures to assess TD, has confirmed the presence of mild TD or odd speech in clinically unaffected relatives of SZ patients 42,44,[81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98] and in high-risk offspring. 20,[99][100][101][102][103][104][105][106] Notably, the biological relatives of SZ (RelSZ) adoptees have significantly higher TD scores than adoptive RelSZ. 92 Similarly, idiosyncratic verbalizations are significantly more prevalent in adopted biological offspring of SZ mothers than in adopted offspring of control mothers.…”
Section: Introductionmentioning
confidence: 99%
“…These data support the concept of disorganized communication as a potential endophenotype or stable trait marker for schizophrenia risk, consistent with the finding that disorganized communication aggregates in family members of individuals with schizophrenia (Levy et al, 2010) and predicts psychosis onset also in genetic high-risk individuals(Ott et al., 2002). Of note, the relevance of subthreshold thought disorder for emergent schizophrenia and related psychotic disorders is evident also from studies of 1) speech analysis, using audio recordings and transcripts, in both clinical high risk (Bearden et al, 2011) and genetic high risk (Gooding et al, 2012; Gooding et al., 2013) cohorts; and 2) studies of speech illusion (the tendency to find spurious meaning in the noise of overlapping speech), which is increased in those CHR participants who go on to develop psychosis (Hoffman et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…N = 52–161) of cohort sizes in prior studies that evaluated trajectories of symptoms in autism, bipolar disorder and psychosis (M’Bailara et al, 2013; Ozonoff et al, 2011; Pelayo-Teran et al, 2014). Future studies including longitudinal assay of structural and functional integrity of the left superior temporal gyrus and its connectivity with other nodes relevant to language, as well as analysis of speech transcripts (Bearden et al, 2011; Gooding et al, 2012; Gooding et al, 2013) and speech interpretation (Hoffman et al, 2007), may carry added benefit. In addition, therapeutics beyond dopamine antagonists, that similarly target the superior temporal gyrus and related neuroanatomic regions (such as noninvasive brain stimulation and/or language-based remediation strategies) may also be considered in conjunction with putative neuroimaging and/or speech analysis biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…the disruption in flow of meaning in language (derailment, tangentiality) 2 . This language disturbance is an early core feature of schizophrenia, evident in subtle form prior to initial psychosis onset, in cohorts of both familial 3 and clinical [4][5][6][7] high-risk youths, as assessed using clinical ratings. Beyond clinical ratings, there has been an effort to characterize early subtle language disturbances in clinical high-risk (CHR) individuals using linguistic analysis, with the aim of improving prediction.…”
mentioning
confidence: 99%